Treatise on Harmony - Rameau, Jean-Philippe 1683-1764; Gossett, Philip (New York Dover publications, 1971)
One of most important books in Western music. Detailed explanation of principles of diatonic harmonic theory. New 1971 translation by Philip Gossett of 1722 edition. Many musical examples.--------------------------------------------------------------------------------
Keywords: Music theory